Microbiome composition and presence of cultivable commensal groups of Southern Tamanduas (Tamandua tetradactyla) varies with captive conditions - Amin, Ahmad; Mekadim, Chahrazed; Modrackova, Nikol; Bolechova, Petra; Mrazek, Jakub; Neuzil-Bunesova, Vera (Animal microbiome, 2024)
Southern Tamanduas (Tamandua tetradactyla) belong to the specialized placental myrmecophages. There is not much information about their intestinal microbiome. Moreover, due to their food specialization, it is difficult to create an adequate diet under breeding conditions. Therefore, we used 16S rDNA amplicon sequencing to analyze the fecal microbiome of captive Southern Tamanduas from four locations in the Czech Republic and evaluated the impact of the incoming diet and facility conditions on microbiome composition. Together with the microbiome analysis, we also quantified and identified cultivable commensals. The anteater fecal microbiome was dominated by the phyla Bacillota and Bacteroidota, while Pseudomonadota, Spirochaetota, and Actinobacteriota were less abundant. At the taxonomic family level, Lachnospiraceae, Prevotellaceae, Bacteroidaceae, Oscillospiraceae, Erysipelotrichaceae, Spirochaetaceae, Ruminococcaceae, Leuconostocaceae, and Streptococcaceae were mainly represented in the fecal microbiome of animals from all locations. Interestingly, Lactobacillaceae dominated in the location with a zoo-made diet. These animals also had significantly lower diversity of gut microbiome in comparison with animals from other locations fed mainly with a complete commercial diet. Moreover, captive conditions of analyzed anteater included other factors such as the enrichment of the diet with insect-based products, probiotic interventions, the presence of other animals in the exposure, which can potentially affect the composition of the microbiome and cultivable microbes. In total, 63 bacterial species from beneficial commensal to opportunistic pathogen were isolated and identified using MALDI-TOF MS in the set of more than one thousand selected isolates. Half of the detected species were present in the fecal microbiota of most animals, the rest varied across animals and locations.
Keywords: Anteater; Diet; Fecal microbiome; Captive environment; Cultivable microbes